Critical success factors for implementing lean manufacturing in Malaysian automotive industry - A. N. M., Rose; B. M., Deros; M. N. A., Rahman (Maxwell Science Publications, 2014)
The challenges faced by automotive manufacturers had made them looked into Lean Manufacturing (LM) which was implemented by Toyota Motor a long time ago. In Malaysia, the two main car manufacturers are PROTON and PERODUA; these two manufacturers offer good opportunity to large local companies and Small Medium Enterprises (SMEs) to participate in the automotive component manufacturing industry. The main objective of this study is to explore and investigate the level of perceptions on the importance and extent of practice with respect to 13 Critical Success Factors (CSFs) for LM implementation. To perform this study, a survey instrument that consists of 13 CSFs and 78 items was developed and distributed to local companies. The comparison was carried out on each of these CSFs based on perception, number of years and company size. The statistical analysis using the Kruskal Wallis test had identified four basic critical success factors for both SMEs and large companies with respect to the perception on the importance and extent of practice. Further study probes into the outcomes of the exploration on feasible LM practices.